2017
DOI: 10.1177/0886260517692996
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Intergenerational Cycle: Partner Violence, Child–Parent Attachment, and Children’s Aggressive Behaviors

Abstract: The link between exposure to violence in the home and children's later exhibition of violent behaviors is well documented in the criminological literature. To date, most research on partner violence (PV) and children's welfare has focused on adolescent outcomes. As such, we know little about how PV affects the behavior of the youngest, and perhaps most vulnerable population of children who have been exposed to PV. Our understanding of the PV-child behavior association is also limited because extant research ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Despite the evidence that insecure attachment is related to abusive and aggressive behaviors, recent longitudinal research with a youth sample (ages 3–9 years; Juan et al, 2020) found a child’s secure attachment to at least one parent did not moderate the relationship between exposure to violence (i.e., partner violence between parents) and the child’s subsequent aggression. This suggests the parent–child attachment failed to buffer the effects of exposure.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Despite the evidence that insecure attachment is related to abusive and aggressive behaviors, recent longitudinal research with a youth sample (ages 3–9 years; Juan et al, 2020) found a child’s secure attachment to at least one parent did not moderate the relationship between exposure to violence (i.e., partner violence between parents) and the child’s subsequent aggression. This suggests the parent–child attachment failed to buffer the effects of exposure.…”
Section: Literature Reviewmentioning
confidence: 96%
“…This buffering effect extended to having the support of others such as extended family, church members, and coworkers. There is much empirical evidence supporting the notion of DP, which can make this concept an important justice-oriented addition to attachment frameworks (De Rubeis et al, 2016; English et al, 2018; Godbout et al, 2017; Gustafsson et al, 2017; Juan et al, 2020; McIntosh et al, 2019; Sagi-Schwartz, 2012).…”
Section: The Kingian Neuro-relational Theorymentioning
confidence: 99%
“…The concept of experience is particularly common in child-oriented research that considers children as agents and subjects. [7,15,22,23]. The emphasis on the notion of experiencing violence is on the holistic nature of the experience of violence and the fact that the consequences of seeing or hearing violence are not limited to the moment of witnessing the situation, as the child can also witness the effects of violence and be made aware of it otherwise [8].…”
Section: Literature Review 21 Children As Witnesses Of Intimate Partner Violencementioning
confidence: 99%